Hybrid Plasmonic Modes in Multilayer Trench Grating Structures. Issue 22 (18th September 2017) - Liu, Xiaoyi; Gao, Jinsong; Yang, Haigui; Wang, Xiaoyi; Tian, Sicong; Guo, Chengli
Abstract: For common plasmonic structures, it is difficult to considerate both the abilities of confining light and reducing loss. Here, two plasmonic multilayer structures comprised of five alternate Al and Si layers are demonstrated. First, the multilayer gratings with near‐infrared dual narrowband peaks are given in the spectrum excited by Fabry–Perot resonance. Through investigating the modes of electric field distributions, the frequency‐sensitivity, and linear designable characteristic of its working bands are clarified. Second, the multilayer trench gratings containing both stripes and trenches, which can induce the cavity effect additionally, are demonstrated. When the incidence is oblique, some new modes can be observed, leading to the C‐S hybrid plasmonic coupling modes. Besides, by changing the length of designed waveguide, the Fabry–Perot resonance modes can successively merge with the cavity effect modes, generating the hybrid modes regularly. As a contrast, their quality factors to evaluate the losses and qualities of designed two structures are calculated, and the results imply that the multilayer trench gratings reduce the loss effectively without decreasing energy localization. Detailed process and significance of calculations are discussed carefully. Abstract : A novel silicon‐based microstructure of multilayer trench grating is demonstrated, which supports two plasmonic energy distributions: the Fabry–Perot resonance modes and the cavity effect modes. Based on them, the hybrid modes can be generated regularly, providing a quite high Q factor, namely, a low Ohmic loss without decreasing the effect of energy confinement simultaneously.